Telehealth mitigates COPD disease progression compared to standard of care: a randomized controlled crossover trial. (11th January 2021) - Rassouli, F.; Germann, A.; Baty, F.; Kohler, M.; Stolz, D.; Thurnheer, R.; Brack, T.; Kähler, C.; Widmer, S.; Tschirren, U.; Sievi, N. A.; Tamm, M.; et al.
Abstract: Background: We showed excellent adherence and satisfaction with our telehealth care (TC) approach for COPD. Here, the results of a consecutive randomized controlled trial are presented. Methods: Patients were randomly assigned to TC or standard care (SC). During TC, patients answered six daily questions online, and focused on the early recognition of exacerbations, in addition to SC. Results: The mean increase in COPD assessment test (CAT) was 1.8 vs. 3.6 points/year in the TC and SC groups, respectively ( P = 0.0015). Satisfaction with care (VAS) at baseline was 8.2; at the end of SC, 8.5 ( P = 0.062); and after TC, 8.8 ( P < 0.001). We detected significantly more moderate exacerbations during TC. Conclusion: Whilst receiving TC, the slope of the CAT increase – an indicator of the naturally progressive course of COPD – was reduced by 50%. Satisfaction with care increased with TC. The higher number of detected moderate exacerbations probably indicates a higher diagnostic sensitivity than without TC.